QUANTIDADE DE BIOMASSA E NUTRIENTES EM SISTEMA AGROFLORESTAL NA LOCALIDADE DE SANTA TEREZA, MUNICÍPIO DE CATUÍPE – RS - Klein, Fátima R. S.; Cavalheiro, Laísa W.; Correa, Geodeli A. P.; Lima, Jonas D. N. d.; Escaio, Ana C.; Coelho, Geraldo C. (Salão do Conhecimento, 2013)
Resumo